On the role of network topology in German-Jewish recommendation letter networks in the early twentieth century - Lisa Gerlach; David B. Blumenthal (Applied Network Science, 2023)
Abstract Recommendation letters were an important instrument for orchestrating Jewish emigration from Germany in the late nineteenth and early twentieth century. Here, we present network-based analyses of manually collected meta-data from recommendation letters targeted at the Hebrew University (HU) in Jerusalem. Using standard semi-supervised node classification techniques and differential node centrality analyses, we show that the position of a recommendation letter in content-agnostic recommendation network models is predictive of its success, i.e., of whether or not the letter led to the recommendee obtaining a position at the HU. In particular, we show that authors of successful recommendation letters assume more central positions within the networks than authors of unsuccessful letters, while the opposite holds for the recommendation letters’ receivers. Beyond our application, these results showcase the potential of using network models for generating historical insights. Both the letter meta-data records and Python code to reproduce our analyses are available on GitHub: https://github.com/bionetslab/corrnet .